Sistem Tracking Pengiriman Barang Pada PT. Afro Angkasa Express Dengan Menggunakan Framework Laravel 8 - Michael Yohanes Wicaksono; Alexander Setiawan; Kartika Gunadi (Jurnal Infra, 2022)
In this era of globalization, it is increasingly common for people to shop and sell their goods online. So that more and more shipping companies are there. With the increasing number of existing freight forwarding companies, PT Afro Angkasa Express must offer convenience and features to attract customers. The design of this goods delivery tracking system is intended to make it easier for PT Afro Angkasa Express customers to track goods. In addition, customers can place orders more easily through the website. Customers will also be provided with features such as on-site pick-up, so that PT Afro Angkasa Express will become one of the community's mainstays for goods delivery solutions. The Laravel 8 framework has advantages compared to other frameworks such as the Templating Engine feature that can design unique layouts and also reduce the impact of XSS (Cross Side Scripting) attacks.